Role of N6-methyladenosine RNA modification in gastric cancer - Si-Qi Ding; Xue-Ping Zhang; Jun-Peng Pei; Xiao Bai; Jin-Jie Ma; Chun-Dong Zhang; Dong-Qiu Dai (Cell Death Discovery, 2023)
Abstract N6-methyladenosine (m6A) RNA methylation is the most prevalent internal modification of mammalian messenger RNA. The m6A modification affects multiple aspects of RNA metabolism, including processing, splicing, export, stability, and translation through the reversible regulation of methyltransferases (Writers), demethylases (Erasers), and recognition binding proteins (Readers). Accumulating evidence indicates that altered m6A levels are associated with a variety of human cancers. Recently, dysregulation of m6A methylation was shown to be involved in the occurrence and development of gastric cancer (GC) through various pathways. Thus, elucidating the relationship between m6A and the pathogenesis of GC has important clinical implications for the diagnosis, treatment, and prognosis of GC patients. In this review, we evaluate the potential role and clinical significance of m6A-related proteins which function in GC in an m6A-dependent manner. We discuss current issues regarding m6A-targeted inhibition of GC, explore new methods for GC diagnosis and prognosis, consider new targets for GC treatment, and provide a reasonable outlook for the future of GC research.